2018
DOI: 10.1002/acr.23580
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of Rheumatoid Arthritis Patients on Electronic Communication and Patient‐Reported Outcome Data Collection: A Qualitative Study

Abstract: Patients with RA may be amenable to electronic collection and sharing of PRO-type data between clinical encounters if it facilitates communication with health care providers, and provides access to reliable information about RA. Providing patients with social support was important for enhancing PROs collection by helping them overcome barriers with using electronic devices and patients' reservations about the value of this data. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
31
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 21 publications
7
31
0
3
Order By: Relevance
“…The results of this study align with previous findings supporting the acceptability of RMT apps for use in RA disease management [ 13 - 15 , 24 ]. Patients approved the development of an app for the purpose of individual symptom tracking.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results of this study align with previous findings supporting the acceptability of RMT apps for use in RA disease management [ 13 - 15 , 24 ]. Patients approved the development of an app for the purpose of individual symptom tracking.…”
Section: Discussionsupporting
confidence: 91%
“…It is not yet clear in the literature whether the perception of remote symptom measurement varies by gender. This is a common limitation, and the gender ratio is similar to other studies in the field [ 24 ]. Third, sampling for qualitative work inevitably results in a selection effect, whereby certain individuals might be more motivated to participate.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Particularly among patients, there is great interest in PROs. Navarro-Millán et al [ 36 ] showed a marked interest among patients in becoming more involved in the therapy and in collecting and sharing ePROs with their doctors when it facilitated communication. Other publications suggest that patients prefer entering ePROs from home [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…[30]. Our previous work showed that patients lost interest in completing PROs if the rheumatologist did not use the provided information [31]. Thus, in the present study, we attempted to identify the information most valued by the rheumatologists to make treatment recommendations for RA so we can further determine which PROs could be utilized to measure it.…”
Section: Discussionmentioning
confidence: 99%